2017
DOI: 10.1021/acs.jpcb.7b04862
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Phosphoryl Transfer Reaction from ATP to Dha Catalyzed by DhaK from Escherichia coli

Abstract: Protein kinases, representing one of the largest protein family involved in almost all aspects of cell life, have become one of the most important targets for the development of new drugs to be used in, for instance, cancer treatments. In this paper an exhaustive theoretical study of the phosphoryl transfer reaction from adenosine triphosphate (ATP) to dihydroxyacetone (Dha) catalyzed by DhaK from Escherichia coli (E. coli) is reported. Two different mechanisms, previously proposed for the phosphoryl transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
(155 reference statements)
3
7
0
Order By: Relevance
“…These values are significantly lower than those reported for the asp‐assisted mechanism in the wild‐type and in the mutated enzyme. This trend is in agreement with our previous study of the phosphate transfer from ATP to Dha catalyzed by DHAK that also showed the substrate‐assisted mechanism as the most favorable one …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…These values are significantly lower than those reported for the asp‐assisted mechanism in the wild‐type and in the mutated enzyme. This trend is in agreement with our previous study of the phosphate transfer from ATP to Dha catalyzed by DHAK that also showed the substrate‐assisted mechanism as the most favorable one …”
Section: Resultssupporting
confidence: 93%
“…In the substrate‐assisted mechanism the poly‐P molecule directly abstracts the proton from Dha. De Vivo et al supported this mechanism in the theoretical study of the phosphate transfer reaction from ATP to a serine residue in CDK2, as well as our previous study of the phosphate transfer reaction from ATP to Dha on wild‐type DHAK . Both reaction mechanisms are explored for the phosphate transfer reaction from poly‐P, instead of ATP, to Dha on wild‐type and E526K mutant in the present study.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations